Aconitum carmichaelii Debeaux: A systematic review on traditional use, and the chemical structures and pharmacological properties of polysaccharides and phenolic compounds in the roots. (12th June 2022) - Fu, Yu-Ping; Zou, Yuan-Feng; Lei, Fei-Yi; Wangensteen, Helle; Inngjerdingen, Kari Tvete
Abstract: Ethnopharmacological relevance: Aconitum carmichaelii, belonging to the Ranunculaceae family, is a widely used traditional herbal plant in Asian countries, especially in China. The lateral ("Fuzi") and mother ("Chuanwu") roots are the two main plant parts used in Traditional Chinese Medicine (TCM), where they are used in the treatment of acute myocardial infarction, heart failure, rheumatoid arthritis, and as analgesics. Aim of the study: In order to further guide the research direction and application of A. carmichaelii, this study aims to give a systematic and in-depth overview on the phytochemical and pharmacological studies of non-alkaloid natural products with focus on polysaccharides and phenolic compounds. Materials and methods: A comprehensive search in the literature was conducted based on the databases Google Scholar, SciFinder (American Chemical Society), Springer Link, PubMed Science, Science Direct and China National Knowledge Internet, Wanfang Data, in addition to books, doctoral and master's dissertations, and official website. The main keywords were: " Aconitum carmichaelii ", "Aconiti Lateralis Radix Praeparata", "Fuzi", "Chuanwu", "Aconiti Radix", "monkshood" and "Bushi". Results: A. carmichaelii is known for the use of its different root parts, including "Fuzi" and "Chuanwu". Different types of polysaccharides, both neutral and acidic, and 39 phenolic compounds like flavonoids, phenylpropanoids, lignans, neolignans, and benzoic acid derivatives have been isolated and identified from the roots. Pharmacological studies of the isolated polysaccharides have demonstrated various biological effects such as hypoglycemic, hypolipidemic, cardiovascular, immunomodulatory, anti-tumor, and neuropharmacological activities. Studies on pharmacological effects of the phenolic compounds isolated from the roots are however limited. Conclusions: This review shows that polysaccharides could be one of the active components in the roots of A. carmichaelii, and they are promising for future applications due to their pharmacological properties. In addition, polysaccharides are generally non-toxic, biocompatible, and biodegradable. This review also sheds light on new research directions for A. carmichaelii . A more detailed structural characterization of polysaccharides from different root parts of A. carmichaelii, and their structure-activity relationships are required. Additionally, their pharmacological properties as immunomodulators in the intestinal system should be investigated. Further, more knowledge about the pharmacological effects and molecular mechanisms of the phenolic compounds that have been identified are needed. Graphical abstract: Image 1